Enabling LiTFSI‐based Electrolytes for Safer Lithium‐Ion Batteries by Using Linear Fluorinated Carbonates as (Co)Solvent. Issue 10 (19th August 2014) - Kalhoff, Julian; Bresser, Dominic; Bolloli, Marco; Alloin, Fannie; Sanchez, Jean‐Yves; Passerini, Stefano
Abstract In this Full Paper we show that the use of lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) as conducting salt in commercial lithium‐ion batteries is made possible by introducing fluorinated linear carbonates as electrolyte (co)solvents. Electrolyte compositions based on LiTFSI and fluorinated carbonates were characterized regarding their ionic conductivity and electrochemical stability towards oxidation and with respect to their ability to form a protective film of aluminum fluoride on the aluminum surface. Moreover, the investigation of the electrochemical performance of standard lithium‐ion anodes (graphite) and cathodes (Li[Ni1/3Mn1/3Co1/3]O2, NMC) in half‐cell configuration showed stable cycle life and good rate capability. Finally, an NMC/graphite full‐cell confirmed the suitability of such electrolyte compositions for practical lithium‐ion cells, thus enabling the complete replacement of LiPF6 and allowing the realization of substantially safer lithium‐ion batteries.